Hypoglycemic, Anti-adipogenic Effect of Soy Husk Phenolic-rich Extract through Inhibition of PPAR? Gene Transcription in Pancreatic Beta and 3T3-L1 Cells - Tan Seok-Tyug; Faisal Ali; Amin Ismail; Chong Pei-Pei; Sun Jian (Elsevier, 2020)
Background Soy husk powder is a rich source of polyphenols that has been traditionally used as the treatment of several types of metabolic-related disease. There is no single medicine available that can manage both glucose and adipogenesis homeostasis. In this study the hypoglycemic and adipogenic potential effect of phenolic-rich soy husk powder extract (SHPE) was investigated in vitro. Methods For evaluation the hypoglycemic activity of SHPE, alpha amylase and alpha glucosidase enzyme inhibition using clonal pancreatic BRIN-BD11 beta cells insulin secretary was examined. On the other side, the murine 3T3-L1 adipocytes were employed for assessing the anti-adipogenic properties of SHPE. Furthermore, the ability of SHPE in mediating the rate of glucose absorption, stimulating insulin secretion and ameliorating insulin resistance were also tested in this study. Results SHPE treatment was significantly reduced the activity of alpha amylase by (48.8%) and alpha glucosidase by (58.3%) compared to the diabetic control in BRIN-BD11 beta cells. In 3T3-L1 adipocytes, SHPE treatment demonstrated significant (p< 0.01) reduction in lipid droplet accumulation, triglyceride accumulation and GPDH activity. Furthermore, mRNA expression level for PPAR? gene was downregulated by the treatment with SHPE in 3T3-L1 adipocytes. Conclusions the inhibition of ?-amylase and ?-glucosidase enzymes as well as the lipid content can significantly reduce the post-prandial increase of blood glucose and therefore can be an important approach in the management of hyperglycemia and dyslipidymia in type 2 diabetic patients.